Jackhammer esophagus: high-resolution manometry and therapeutic approach using peroral endoscopic myotomy (POEM). Issue 6 (1st September 2016) - Kandulski, A.; Fuchs, K.-H.; Weigt, J.; Malfertheiner, P.
Summary: We present the first report on peroral endoscopic myotomy (POEM) in the treatment of jackhammer esophagus. A 34-year-old female patient was newly diagnosed with a jackhammer esophagus. After failure of medical treatment, the patient underwent POEM procedure for myotomy of the spastic segment. Postoperatively, a mild emphysema and pneumothorax occurred that required drainage and antibiotic therapy until full recovery. Discharge was possible after 5 days. Six months later, she presented with recurrent but mild pain due to a remnant spastic segment proximal to the myotomy. Endoscopic balloon dilation was performed twice within 6 weeks with full symptomatic relief of pain and mild symptoms of dysphagia.